Evaluating a Generic Feasibility Model for Startups in India - Darbha, Satish (Digital Repository of Theses, 2024)
This study aims to evaluate the effectiveness of a generic feasibility model for startups in India. The research assesses the applicability and relevance of the model in the Indian startup ecosystem, considering factors such as market dynamics, regulatory environment, and cultural nuances. Through a combination of qualitative and quantitative analysis and existing literature review, the study seeks to provide insights into the potential benefits and limitations of adopting such a model for aspiring entrepreneurs in India. The findings contribute to the ongoing discourse on enhancing startup success rates and fostering innovation within the Indian entrepreneurial landscape. The implications of feasibility models will allow practitioners to identify and mitigate potential risks associated with a startup idea. This helps in making informed decisions and reducing the chances of failure and will aid practitioners in creating a roadmap for the startup, outlining key milestones, goals, and strategies for growth.